Staphylococcus aureus enterotoxin‐specific IgE is associated with asthma in the general population: a GA2LEN study. Issue 10 (5th October 2013) - Tomassen, P.; Jarvis, D.; Newson, R.; Van Ree, R.; Forsberg, B.; Howarth, P.; Janson, C.; Kowalski, M. L.; Krämer, U.; Matricardi, P. M.; Middelveld, R. J. M.; Todo‐Bom, A.; et al.
Abstract Background Specific IgE to Staphylococcus aureus enterotoxins (SE‐IgE) has been associated with asthma. In the general population, we aimed to determine the prevalence of and risk factors for serum SE‐IgE and to examine the association with asthma. Methods A postal questionnaire was sent to a random sample of adults in 19 centers across Europe. A random sample of respondents was invited for clinical examination upon which they answered a questionnaire, underwent skin prick tests (SPTs) for common aeroallergens, and provided blood for measurement of total IgE and SE‐IgE. Risks were analyzed within centers using weighted logistic regression, and overall estimates calculated using fixed‐effects meta‐analysis. Results 2908 subjects were included in this analysis. Prevalence of positive SE‐IgE was 29.3%; no significant geographic variation was observed. In contrast to positive skin prick tests, SE‐IgE was more common in smokers (<15 pack‐year: OR 1.11, P = 0.079, ≥15 pack‐year: OR 1.70, P < 0.001), and prevalence did not decrease in older age‐groups or in those with many siblings. Total IgE concentrations were higher in those with positive SE‐IgE than in those with positive SPT. SE‐IgE was associated with asthma (OR 2.10, 95% confidence interval [1.60–2.76], P = 0.001) in a concentration‐dependent manner. This effect was independent of SPT result and homogeneous across all centers. Conclusions We report for the first time that SE‐IgE is common in the general population throughout Europe and that its risk factors differ from those of IgE against aeroallergens. This is the first study to show that SE‐IgE is significantly and independently associated with asthma in the general population.